Possibilities of using spelling manuals in the teaching of the Croatian language - Božanić, Petra; Nemeth-Jajić, Jadranka (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
The paper primarily draws attention to the need for regular use of spelling manuals in the teaching of the Croatian language. Namely, students learn the spelling norm mainly from secondary sources, i.e., from Croatian language textbooks in which spelling content is functionally connected with grammatical content, while the use of spelling (spelling manuals) as a primary source in teaching is often neglected. Such a practice does not favor the acquisition of the habit of spelling, which is important for every educated citizen, regardless of his occupation. In accordance with the observed problem, the paper also considers and exemplifies the possibilities of using spelling manuals in the teaching of the Croatian language. This also contributes to the achievement of one of the tasks of teaching Croatian spelling, which is to teach students to use spelling manuals so that they can independently find examples, rules and answers to spelling doubts.